Involvement of nitric oxide through endocannabinoids release in microglia activation during the course of CNS regeneration in the medicinal leech. Issue 4 (28th January 2013) - Arafah, Karim; Croix, Dominique; Vizioli, Jacopo; Desmons, Annie; Fournier, Isabelle; Salzet, Michel
Abstract The medicinal leech is notable for its capacity to regenerate its central nervous system (CNS) following mechanical trauma. Using an electrochemical nitric oxide (NO)‐selective electrode to measure NO levels, we found that the time course of NO release in the injured leech CNS is partially under the control of endocannabinoids, namely, N‐arachidonyl ethanolamide (AEA) and 2‐arachidonyl glycerol (2‐AG). Relative quantification of these endocannabinoids was performed by stable isotope dilution (2AGd8 and AAEd8) coupled to mass spectrometry in course of regeneration process or adenosine triphosphate (ATP) treatment. Data show that 2‐AG levels rose to a maximum about 30 min after injury or ATP treatment, and returned to baseline levels 4 h after injury. In same conditions, AEA levels also rapidly (within 5 min) dropped after injury or ATP treatment to the nerve cord, but did not fully return to baseline levels within 4 h of injury. In correlation with these data, chemoattraction activities of endocannabinoids on isolated leech microglial cells have been shown in vitro and in vivo reflecting that control over NO production is accompanied by the controlled chemoattraction of microglia directed from the periphery to the lesion site for neuronal repair purposes. Taken together, our results show that in the leech, after injury concurrent with ATP production, purinergic receptor activation, NO production, microglia recruitment, and accumulation to lesion site, a fine imbalance occurs in the endocannabinoid system. These events can bring explanations about the ability of the leech CNS to regenerate after a trauma and the key role of endocannabinoids in this phenomenon. © 2013 Wiley Periodicals, Inc. © 2013 Wiley Periodicals, Inc.